PERAN UNITED NATIONS DEVELOPMENT PROGRAMME (UNDP) DALAM PERJUANGAN HAK ASASI MANUSIA KOMUNITAS LESBIANS, GAY, BISEKSUAL DAN TRANSGENDER (LGBT) DI INDONESIA - Zulhadi Kunfay; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study discusses “The Role of The United Nations Development Programme (UNDP) in The Human Rights Struggle of The LGBT Community in Indonesia”. Many LGBT people in Indonesia experience violence, discrimination and human rights violations, because there are no Indonesian Government regulations that provide rights to security and the right to freedom of assembly and association for LGBT people. As a result this problem, UNDP provides assistance to the LGBT community in Indonesia.            The method use in this study is qualitative explanative. This study uses secondary data using libray research. This study uses the Perspective of Pluralism by Paul R, Viotti and Mark V. Kauppi, Level Analysis of Group Behaviour and Theories of International Organization by J. Clive and Role Theory by Samuel J Barkin.            The result of this research is the role of the UNDP in fighting for the LGBT community in Indonesia such as advocacy, dialogue, providing understanding, campaigning and providing assistance to the LGBT community in Indonesia. UNDP fights for human rights by creating the "Being LGBT in Asia" program and providing financial assistance to the LGBT community in Indonesia. Keywords : LGBT, Pluralism, Human Right, UNDP, Indonesia.